Investigating petroleum oil bioremediation strategies for crude oil contaminated mining sites in Mpumalanga, South Africa - Venter, S.N. (Stephanus Nicolaas) (University of Pretoria, 2016)
Mini Dissertation (MSc)--University of Pretoria, 2015.